Gonadal dysgenesis in a 46, XY female mosaic for double autosomal trisomies 8 and 21. Issue 4 (August 1980) - Sulewski, J M; Thao-phuong-Dang,; Ward, S; Ladda, R L
Abstract : The proband was evaluated at 19 years of age because of primary amenorrhoea and, on chromosomal analysis, was found to have a 46, XY karyotype in 75% of her cells and 48, XY, +8, +21 in 25% of her cells. She appeared normal at birth and exhibited normal intellectual and physical development until puberty when secondary sexual differentiation failed. This young women showed none of the dysmorphic features associated with either trisomy 8 or trisomy 21. Her XY gonadal dysgenesis was manifested by late developmental problems of amenorrhoea, sexual infantilism, and gonadal neoplasia.